1984
DOI: 10.1002/j.1460-2075.1984.tb01797.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of self-assembly of the multi-enzyme complex tryptophan synthase from Escherichia coli.

Abstract: The a subunit is bound with negative cooperativity to the holo(2 subunit of tryptophan synthase in phosphate buffer.Thus it is feasible to measure separately the rates of formation both of the stable aC32 subcomplex from O2, and of the mature a2f32 complex from rn2, using stopped-flow techniques. Addition of each a subunit proceeds in two steps; an initial cx, protomer is formed rapidly, which subsequently isomerizes slowly to the equilibrium state. The rates of dissociation of both the 0a2 and a2/2 complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Considerable evidence exists demonstrating that in the TSase enzyme complex the active sites of the enzyme subunits are cross-activated by bound substrates (35,36) and that substrate binding increases subunit association (34 -36). L-Serine, the ligand of TrpB, following conversion to an aminoacrylate intermediate, is believed to induce a conformational change in TrpB that is communicated to the active site of TrpA, leading to activation of cleavage of InGP at the TrpA active site (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable evidence exists demonstrating that in the TSase enzyme complex the active sites of the enzyme subunits are cross-activated by bound substrates (35,36) and that substrate binding increases subunit association (34 -36). L-Serine, the ligand of TrpB, following conversion to an aminoacrylate intermediate, is believed to induce a conformational change in TrpB that is communicated to the active site of TrpA, leading to activation of cleavage of InGP at the TrpA active site (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…L-Serine, the ligand of TrpB, following conversion to an aminoacrylate intermediate, is believed to induce a conformational change in TrpB that is communicated to the active site of TrpA, leading to activation of cleavage of InGP at the TrpA active site (35,36). Similarly, InGP, the substrate of TrpA, increases TrpA's association with TrpB and greatly stimulates TrpB's activity in the indole ϩ serine 3 tryptophan reaction (36). ␣-Glycerophosphate, a TrpA substrate analog, also can increase TrpB enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutual activation is considered to result from conformational changes in both subunits induced by subunit association. The conformational change in both subunits upon complex formation has been suggested by kinetic studies (Lane et al, 1984), calorimetry (Wiesinger et al, 1979), small-angle X-ray scattering (Wilhelm et al, 1982), fluorescence and hydrodynamic measurements (Lane, 1983 ;Lane et al, 1984;Lane and Kirschner, 1983), neutron scattering (Ibel et al, 1985), and immunochemical studies with monoclonal antibodies against the j? subunit (Murry-Brelier and Goldberg, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that there are absorbance and fluorescence changes exhibited by the pyridoxal phosphate upon reaction with serine and chemical nature of the serine-pyridoxal phosphate complexes have been defined (Faeder and Hammes, 1971;York, 1972;Lane and Kirschner, 1983;Lane et al, 1984;Drewe and Dunn, 1985). In the first step, serine displaces the internal aldimine formed between Lys-87 and the pyridoxal phosphate at the active site of the ␤ subunit to form the external aldimine (E-Ser in Schemes II and III), which is highly fluorescent, with emission at 500 nm upon excitation at 405 nm.…”
mentioning
confidence: 99%